ACADEMIC COLLABORATIONS AND GENERAL BALANCE OF HISTORIOGRAPHIC PRODUCTION IN SCIENCE, TECHNOLOGY, AND ENVIRONMENT IN COSTA RICA - Chavarría Camacho, David (2019)
This article realizes a general characterization and systematization of the main academic research that deals with historical processes and their relationship with the emergence and development of scientific, technological, environmental phenomena in Costa Rica. This paper discusses the main problems raised by these authors, the general themes of their research, and some academic links and collaborations between them, which allows us to approach a general diagnosis of the state of knowledge in these fields of study. To carry out this article, some graphic methods were used to analyze the associations between the researchers, which allows to determine the more general components of the intellectual structure of the participants of the academic production. The research considers three main components in this process: 1) the research studies that deals with the history of the institutionalization of scientific disciplines; 2) those who carry out a historical analysis of the relationship between human beings and nature in Costa Rica, and 3) the works that analyze technique, technology, and the environment in Costa Rican agrarian history.